The expression of androgen-responsive genes is up-regulated in the epithelia of benign prostatic hyperplasia - O’Malley, Katherine J. (2009)
BACKGROUND: Benign prostatic hyperplasia (BPH) is one of the most common diseases among aging men in the United States. In addition to aging, the presence of androgens is another major risk factor in BPH development. However, whether androgen signaling is altered in BPH remains unclear. To determine androgen signaling in BPH, we characterized the expression of 4 different androgen-responsive genes, Eaf2/U19, ELL2, FKBP5, and PSA, in BPH and adjacent normal glandular epithelial cells. METHODS: A set of 17 BPH specimens were from patients over 60 years of age with clinical symptoms of BPH. Laser-capture microdissection (LCM) was used to isolate glandular epithelial cells from BPH areas and adjacent normal areas, separately. LCM isolated cells from individual specimens were lysed and RNA isolation, reverse transcription, and real-time PCR were performed using CellsDirect(™) One-Step qRT-PCR Kit (Invitrogen, Carlsbad, CA). RESULTS: All of the assayed genes displayed increased expression from ~2-fold to ~6-fold, in BPH as compared to the adjacent normal epithelial cells. We also generated a composite androgen response index based on the expression levels of the 4 genes, which provides a reliable readout for overall androgen action. Our study showed that the composite androgen response index in BPH is ~4-fold as compared to that in the adjacent normal tissues. CONCLUSIONS: Androgen signaling is significantly elevated in BPH relative to the adjacent normal prostate. Understanding the mechanisms causing elevated androgen signaling may lead to novel approaches for prevention and/or treatment of BPH.